2005
DOI: 10.17221/5631-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium subsp. paratuberculosis in powdered infant milk: paratuberculosis in cattle - the public health problem to be solved

Abstract: Fifty one products of dried milk baby food purchased from 10 producers from seven countries available on the Czech market have been tested. IS900, the specific fragments for Mycobacterium avium subsp. paratuberculosis (MAP) have been detected using PCR in 25 samples (49.0 %) and fragment f57 by real time PCR in 18 samples (35.3%). These results correspond to the epidemiological situation in Europe and are not unexpected. Paratuberculosis in cattle was almost unknown in the Czech Republic until 1990. An increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…One study evaluated several European brands of infant formula by PCR for M. paratuberculosis and found a high prevalence; however none of the samples were culture-positive (Hruska et al, 2005). A small case control study identified M. paratuberculosis by culture from the breast milk of mothers affected by Crohn's disease, but not from control mothers, demonstrating that M. paratuberculosis may be excreted in breast milk, and that this excretion may be associated with Crohn's disease (Naser et al, 2000).…”
Section: Paratuberculosis In Food For Human Consumptionmentioning
confidence: 99%
“…One study evaluated several European brands of infant formula by PCR for M. paratuberculosis and found a high prevalence; however none of the samples were culture-positive (Hruska et al, 2005). A small case control study identified M. paratuberculosis by culture from the breast milk of mothers affected by Crohn's disease, but not from control mothers, demonstrating that M. paratuberculosis may be excreted in breast milk, and that this excretion may be associated with Crohn's disease (Naser et al, 2000).…”
Section: Paratuberculosis In Food For Human Consumptionmentioning
confidence: 99%
“…A recent, smaller but somewhat parallel study shows that exposure to the hydrolyzed infant formula resulted in lessened incidence of T1DM (Knip et al, 2010). Antibodies against specie specific MAP proteins were found in Sardinian children involved in the TRIGR study (Sechi, personal communication) As previously mentioned, viable MAP has been found in infant formula powder (Hruska et al, 2005).…”
Section: T1dm and Milkmentioning
confidence: 82%
“…Mycobacterium avium ss. paratuberculosis (MAP)is present in pasteurized milk (Millar et al, 1996;Ellingson et al, 2005), infant formula made from pasteurized milk (Hruska et al, 2005), surface water (Pickup et al, 2005;Whan et al, 2005;Pickup et al, 2006), soil (Pickup et al, www.intechopen.com Environmental Triggers of Type 1 Diabetes Mellitus -Mycobacterium Avium Subspecies Paratuberculosis 235 2005), cow manure ''lagoons'' that can leach into surface water, cow manure in both solid and liquid forms that is applied as fertilizer to agricultural land (Grewal et al, 2006), and municipal tap water , providing multiple routes of transmission to humans. In a recent study in Ohio the DNA of MAP was detected in over 80% of domestic water samples (Beumer et al, 2010).…”
Section: Map and Human Exposurementioning
confidence: 99%
“…Economic losses may increase in MAP-infected herds due to an increasing number of studies focused on the hypothesis that there is a causal association between MAP and a Crohn's disease (Thompson, 1994;Hermon-Taylor et al, 2000;Hruska et al, 2005). These economic effects may be caused by milk price reduction as a consequence of consumers' fears.…”
Section: Discussionmentioning
confidence: 99%